(untitled) (Journal of Chitwan Medical College, 2026)
Introduction: Laparoscopic Appendectomy (LA) is increasingly used for acute appendicitis. Securing the appendicular stump remains a critical and debated issue. The Endoloop (EL) is a safe, reliable, cost-effective suture ligation compared to the Harmonic Scalpel (HS), which utilizes an advanced ultrasonic device to provide faster sealing. This study aimed to compare the clinical outcomes and efficiency of the EL versus the HS for stump closure in a resource-constrained setting. Method: A prospective observational comparative study was conducted at Chitwan Medical College, Nepal, from Jul to Dec 2025 after ethical approval. Patients undergoing LA were alternately allocated to EL or HS groups. Primary outcomes were surgery time and hospital stay. Data normality was verified using the Shapiro-Wilk test. Continuous variables (mean±SD) were compared using the independent t-test; categorical variables using the chi-square test in IBM SPSS v20.0. A p-value <0.05 was considered significant. Result: A total of 70 patients were included for analysis (EL group, n=38; HS group, n=32). The mean age was comparable between the EL (36.34±17.62 years) and HS (36.69±16.64 years) groups (p=0.933). The HS group had a significantly shorter mean surgery time (32.34±7.21 min) versus the EL group (48.95±8.47 min; p<0.001). Mean hospital stay was also shorter in the HS group (2.09±0.82 days vs. 3.26±1.48 days; p<0.001). Rates of surgical site infection (p=0.589) and conversion to open surgery (p=0.625) did not differ significantly between groups. Conclusion: Both EL and HS are safe for appendicular stump closure. The HS has advantages of reduced operative time and hospital stay.